Research on rescuers’ training process in toxic / explosive / flammable environments - Gireadă Andrei-Lucian; Ilie Cosmin; Irimia Alin (MATEC Web of Conferences, 2022)
The paper presents the structuring of physical effort put in by rescuers during training, taking into account the activity specific psychosocial factors, structuring that aimed at streamlining the training process of intervention and rescue personnel in toxic / explosive / flammable environments. Training routes with various degrees of difficulty, allowing the simulation of intervention activities in horizontally and vertically confined spaces, low visibility, high temperature and humidity environments were analysed, for each the specific labour consumption being calculated. A dysfunctional phenomenon caused by the intervention and rescue activity is fatigue, perceived as a body reaction to readjust and restore its functions following intense or repeated body requests for energy consumption. Not only physical fatigue (which can be controlled through exercises) is specific for rescue and intervention activity but also mental fatigue. In addition to physical and technical training, psychosocial training of people who carry out intervention and rescue activities was followed in the training programs.